Unmanned and autonomous ground vehicle - S. George Fernandez; K. Vijayakumar; R Palanisamy; K. Selvakumar; D. Karthikeyan; D. Selvabharathi; S. Vidyasagar; V. Kalyanasundhram (Institute of Advanced Engineering and Science, 2019)
Unmanned and Autonomous Ground Vehicle (UAGV) is a smart vehicle that capable of doing tasks without the need of human operator. The automated vehicle can work during off and on road navigation and also used in military operation such as detecting bombs, border patrol, carrying cargos, search, rescue etc reducing soldier’s exposure to danger, freeing them to perform other duties. This type of vehicle mainly uses sensors to observe the environment and automatically take decisions on its own in unpredictable situation and with unknown information or pass this information to the operator who control the UAGV through various communication when it requires support. This UAGV can send visual feedbacks to the operator at the ground station. An onboard sensor gives the complete environment of the vehicle as signals to the operator.